(untitled) (Journal of Innovative Research, 2024)
This paper tried to explore the roles of non-government organizations in developing the skills of street food microentrepreneurs in health and safe food preparation and servicing in the western part of Bangladesh. The study utilized a qualitative approach, using a purposive sampling method to select respondents for in-depth interviews, key informant interviews, and focus group discussions. The street food vendors and stakeholders were selected from the project team, and the research tools included in-depth interviews with 20 vendors, interviews with 8 key stakeholders, and two focus group discussions with customers and entrepreneurs. The researcher discovered that NGO plays a critical role in skill development for street food vendors in Bangladesh. Prior to the project, vendors were unfamiliar with safety, hygiene, cleanliness, and sustainable promotion. The project improved their skills in safety and security, market promotion, hygiene maintenance, cleanliness, and sustainable development by implementing various activities like training, meetings, workshops, food festivals and fairs, market linkage, stakeholder involvement, online and offline market promotion, and so on. The project also increased restaurant customers and market creation. However, the study found that food safety NGO workers and street food programs have collaborated to raise awareness about food safety, health, hygiene, and environmental issues. These initiatives have improved health and lifestyles, improved food quality, increased client numbers, and increased business profits. The stakeholders gathering in Bogura and Rajshahi focused on promoting product certification, with some microenterprises pursuing it. Microenterprises received work-based training on food safety and hygiene, leading to advancements in food packaging, safe raw materials, cleanliness, and hygiene practices. Product certification training increased stakeholders’ understanding of the importance of certification, and some MEs are now following it. The NGO organized a fair to highlight reputable food businesses and raise awareness of environmental sustainability, hygiene, and food safety. The entrepreneurs know how to prepare healthy dishes, increasing sales and revenue. This awareness have been raised due to the NGO’s interventions implemented for street food vendors in the study area.